Crystalline radical polymerizable composition for molding, granule made of the composition, molding made of the granule, and method for producing the molding
The crystalline radical polymerizable composition for molding, featuring a crystalline radical polymerizable compound, inorganic filler, silane coupling agent, and radical polymerizable initiator, addresses the challenges of high thermal conductivity reducing flowability and poor storage stability in existing thermally conductive resin compositions, achieving excellent thermal conductivity and handling properties.
Patent Information
- Application Number
- JP2023158369
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
AI Technical Summary
Existing thermally conductive resin compositions face challenges with high thermal conductivity leading to reduced flowability and poor formability, along with high costs and limited versatility due to the need for large amounts of expensive fillers. Additionally, known compositions like BMCs have poor storage stability and require specialized molding machines.
A crystalline radical polymerizable composition for molding is developed, comprising a crystalline radical polymerizable compound with a glass transition point and melting point, an inorganic filler such as aluminum nitride, a silane coupling agent, and a radical polymerizable initiator. This composition is designed to maintain a solid state at 23°C and achieve a thermal conductivity of 1.0 W/m·K or more.
The composition achieves excellent thermal conductivity and handling properties, ensuring good flowability during molding and providing a cost-effective solution with improved versatility compared to traditional compositions. It also maintains stability and can be molded using standard equipment, addressing the limitations of previous technologies.
Smart Images

Figure 2025049884000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a crystalline radically polymerizable composition for molding, a molded article obtained by molding the composition, a granular material made of the crystalline radically polymerizable composition for molding, and a method for producing the molded article. [Background technology]
[0002] Electrical and electronic components used in automobiles and electrical appliances deteriorate due to heat generated by the components. For this reason, metal wiring and metal cases such as aluminum are used to effectively disperse heat. Metal cases can be over-specified, and there are also demands for productivity, freedom of shape, and insulation, so they are increasingly being replaced by resins. In addition, when using resin materials, a large amount of inorganic filler must be added to impart thermal conductivity, so thermosetting resins with low resin viscosity and excellent heat resistance are used.
[0003] For these reasons, a thermally conductive resin composition has been known (Patent Document 1). Also, an unsaturated polyester resin composition and an enclosed motor have been known (Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6041157 [Patent Document 2] Patent No. 5727628 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the above Patent Document 1, since a thermally conductive filler having an uneven surface is used, the resin composition has a high thermal conductivity. Generally, molding materials with high thermal conductivity contain a large amount of thermally conductive filler, which reduces fluidity and hence causes poor moldability, limiting their applications. In addition, materials with high thermal conductivity and insulating properties are expensive, which limits their versatility and applications.
[0006] In the above Patent Document 2, since BMC (bulk molding compound) requires a dedicated injection molding machine, it is necessary to prepare a dedicated molding machine. In addition, BMC has poor storage stability, and there are problems such as gelation occurring in the summer.
[0007] Therefore, an object of the present invention is to provide a crystalline radically polymerizable composition that is easy to handle. [Means for solving the problem]
[0008] The present inventors have conducted extensive research from various standpoints on compositions containing at least a crystalline radically polymerizable compound, and as a result have discovered the crystalline radically polymerizable composition for molding of the present invention.
[0009] That is, the crystalline radically polymerizable composition for molding of the present invention is a crystalline radically polymerizable composition comprising a crystalline radically polymerizable compound having at least a glass transition point and a melting point, an inorganic filler, a silane coupling agent, and a radical polymerization initiator, wherein the crystalline radically polymerizable composition contains 0.1 to 15 mass% aluminum nitride as an inorganic filler and is a solid at 23°C.
[0010] In addition, in a preferred embodiment of the crystalline radically polymerizable composition for molding of the present invention, the crystalline radically polymerizable compound comprises one or more compounds selected from the group consisting of crystalline unsaturated polyesters, crystalline epoxy (meth)acrylates, crystalline urethane (meth)acrylates, crystalline polyester (meth)acrylates, crystalline polyether (meth)acrylates, crystalline radically polymerizable monomers, and crystalline radically polymerizable multimers.
[0011] In a preferred embodiment of the crystalline radically polymerizable composition for molding of the present invention, the crystalline radically polymerizable compound has a melting point in the range of 30 to 150°C.
[0012] In a preferred embodiment of the crystalline radically polymerizable composition for molding of the present invention, the inorganic filler is contained in an amount of 40 to 95% by mass based on the total amount of the crystalline radically polymerizable composition.
[0013] In a preferred embodiment of the crystalline radically polymerizable composition for molding of the present invention, the ratio of the crystalline radically polymerizable compound to the total amount of the radically polymerizable compounds is 25 parts by mass or more.
[0014] In a preferred embodiment of the crystalline radically polymerizable composition for molding of the present invention, the crystalline radically polymerizable compound has a weight average molecular weight of 70 to 100,000.
[0015] The granular material of the present invention is characterized in that it is made of the crystalline radically polymerizable composition for molding of the present invention.
[0016] The molded article of the present invention is characterized in that it is obtained by molding granules made of the crystalline radically polymerizable molding composition of the present invention.
[0017] In a preferred embodiment of the molded article of the present invention, the molded article has a thermal conductivity of 1.0 W / m·K or more.
[0018] In addition, the method for producing a molded body of the present invention is characterized by having a molding step of molding a molded body by any one of injection molding, transfer molding, compression molding, or hot melt molding using the granules consisting of the crystalline radical polymerizable composition for molding of the present invention. Effect of the Invention
[0019] The crystalline radical polymerizable composition for molding of the present invention has the effect of being excellent in thermal conductivity and ease of handling. Furthermore, the manufacturing method of the present invention has the advantageous effect of providing a radical polymerizable composition with low viscosity when heated and melted during injection molding or transfer molding, thereby ensuring the necessary fluidity during molding. Also, a molded article molded from the crystalline radical polymerizable composition for molding of the present invention can be provided.
[0020] Furthermore, a method for producing a molded article can be provided by using a granule, powder, or tablet made of the crystalline radically polymerizable molding composition of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The crystalline radical polymerizable composition for molding of the present invention is characterized by containing at least a crystalline radical polymerizable compound, an inorganic filler, a silane coupling agent, and a radical polymerization initiator. This is because, by using the crystalline radical polymerizable composition, it is possible to realize a polymerizable composition having excellent thermal conductivity and handling properties, as shown in the examples described below. In this specification, the crystalline radical polymerizable composition for molding may be referred to as a crystalline radical polymerizable composition. In addition, the crystalline radical polymerizable composition for molding of the present invention can also be used for automobile drive motors as one of the molding applications. In addition, an example of a molded body molded from the composition of the present invention is a molded body for automobile drive motors.
[0022] In a preferred embodiment of the crystalline radical polymerizable composition for molding of the present invention, the thermal conductivity of the molded body obtained by molding the crystalline radical polymerizable composition for molding is 1.0 W / m·K or more. The reason for the above range is that, from the viewpoint of heat dissipation, if the thermal conductivity is less than 1.0 W / m·K, the parts including the molded body may accumulate heat and cause malfunction. Conventionally, in order to increase thermal conductivity, a thermally conductive filler with unevenness has generally been used, but molding materials with high thermal conductivity tend to have limited applications due to the reduced fluidity caused by the incorporation of a large amount of thermally conductive filler, and the price tends to be high. However, according to the present invention, it has been found that a sufficiently high thermal conductivity can be obtained, the fluidity is good, and the handling is excellent.
[0023] In a preferred embodiment of the crystalline radical polymerizable composition for molding of the present invention, the crystalline radical polymerizable compound can include one or more selected from crystalline unsaturated polyester, crystalline epoxy (meth)acrylate, crystalline urethane (meth)acrylate, crystalline polyester (meth)acrylate, crystalline polyether (meth)acrylate, crystalline radical polymerizable monomer, and crystalline radical polymerizable multimer. The use of these polymerizable compounds improves mechanical properties and handling (hereinafter, crystallinity may be omitted).
[0024] In this specification, the crystalline compound, including the crystalline radical polymerizable compound, can be a compound having a glass transition point and a melting point. These temperatures can be confirmed by a thermal analyzer such as DSC (differential scanning calorimeter) or TGDTA (thermogravimetric differential thermal analyzer). The crystalline compound in the present invention can be a compound whose melting point can be confirmed by a thermal analyzer.
[0025] In a preferred embodiment of the molding crystalline radical polymerizable composition of the present invention, the crystalline radical polymerizable compound has a melting point of 30 to 150 ° C., more preferably 30 to 120 ° C., from the viewpoint of workability and moldability. Compared with the use of a crystalline radical polymerizable compound having a melting point of less than 30 ° C. or a crystalline radical polymerizable compound having a melting point of more than 150 ° C., the use of a crystalline radical polymerizable compound having a melting point in the range of 30 to 150 ° C. can realize better handling. If the melting point of the crystalline radical polymerizable compound is lower than the above range, it is likely to become liquid at room temperature, so that the crystalline radical polymerizable composition may be difficult to maintain as a solid. If the melting point of the crystalline radical polymerizable compound is higher than the above range, it is close to the molding temperature of the mold, so that the time from the start of flow to hardening is shortened, and molding defects may occur.
[0026] Furthermore, when only a crystalline radical polymerizable compound having a melting point of less than 30° C. is used, it is difficult to obtain a crystalline radical polymerizable composition that is solid at 23° C. On the other hand, when only a crystalline radical polymerizable compound having a melting point of more than 150° C. is used, the composition tends to be less stable because the cylinder temperature and the mold temperature are close to each other when the crystalline radical polymerizable composition is plasticized in the cylinder during injection molding, and therefore a curing reaction may proceed in the cylinder.
[0027] In a preferred embodiment of the crystalline radical polymerizable composition for molding of the present invention, the crystalline radical polymerizable composition is preferably solid at 23°C from the viewpoint of the handling of the crystalline radical polymerizable compound. The reason for the above range is that the shape of the composition does not change under the manufacturing, molding, and transportation environment of the crystalline radical polymerizable composition, so that continuous production is possible using general-purpose manufacturing equipment and conditions. Note that a solid can be one whose shape and volume do not change easily due to an external force.
[0028] In a preferred embodiment of the crystalline radical polymerizable composition for molding of the present invention, the inorganic filler is 40 to 95% by mass, more preferably 50 to 93% by mass, and even more preferably 60 to 90% by mass, based on the total amount of the crystalline radical polymerizable composition, from the viewpoint of product quality. The reason for the above range is that if the amount of the inorganic filler is less than the above range, the shrinkage rate is large and the molded product is deformed, and if the amount is more than the above range, the melt viscosity during molding is high, resulting in unfilled or gas burning in part of the molded product, which may cause carbonization.
[0029] In a preferred embodiment of the crystalline radical polymerizable composition for molding of the present invention, the ratio of the crystalline radical polymerizable compound to the total amount of radical polymerizable compounds can be 25 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 35 parts by mass or more, from the viewpoint of maintaining the solid state. The reason for the above range is that if the ratio of the crystalline radical polymerizable compound is less than the above range, it may be difficult to become solid. In the case of the composition of the present invention, it is possible to make the viscosity high, so that the degree of freedom can be increased to a certain extent. The radical polymerizable compound can include a crystalline radical polymerizable compound and an amorphous radical polymerizable compound, and here, one example of a preferred embodiment of the ratio of the crystalline radical polymerizable compound to the total amount of these radical polymerizable compounds is specified.
[0030] In addition, in a preferred embodiment of the crystalline radical polymerizable composition for molding of the present invention, from the viewpoint of quality control of the crystalline radical polymerizable composition, the weight average molecular weight of the crystalline radical polymerizable compound can be 70 to 100,000, more preferably 100 to 50,000, and even more preferably 150 to 30,000. The reason for the above range is that if the weight average molecular weight of the crystalline radical polymerizable compound is smaller than the above range, the crystalline radical polymerizable composition may not be easily solidified, and if it is larger than the above range, the molecular weight of the crystalline radical polymerizable composition cannot be controlled with high precision, so that the compound characteristics and composition characteristics may vary.
[0031] In a preferred embodiment of the molded article of the present invention, the molded article is made from the crystalline radically polymerizable molding composition of the present invention.
[0032] In a preferred embodiment of the molded article of the present invention, the thermal conductivity of the molded article is equal to or greater than 1.0 W / m K, and more preferably equal to or greater than 1.2 / m K. The reason for specifying the above range is that, from the viewpoint of heat dissipation, if the thermal conductivity is smaller than the above range, the molded article may accumulate heat and cause malfunction.
[0033] In a preferred embodiment of the granules of the present invention, the granules are made of the crystalline radical polymerizable composition for molding of the present invention. Although the granules are used, the present invention may be made of powders, tablets, pellets, etc., in addition to the granules. That is, in the case of other than the granules, the powders, tablets, pellets, etc. of the present invention may be made of the crystalline radical polymerizable composition for molding of the present invention.
[0034] In a preferred embodiment of the method for producing a molded article of the present invention, the method includes a molding step of molding a molded article by injection molding, transfer molding, compression molding, or hot melt molding using the granules made of the crystalline radical polymerizable composition for molding of the present invention. Injection molding is preferred because it allows production in a short time, while transfer molding is preferred because it allows a large amount of products to be obtained at one time.
[0035] The molded article of the present invention is characterized in that a magnet is fixed using the crystalline radical polymerizable composition for molding of the present invention. The fixing method is not particularly limited and may be any conventional method, as long as the crystalline radical polymerizable composition for molding of the present invention is used.
[0036] A composition with low melt viscosity and good fluidity is soft even at room temperature, and thus may cause problems in handling. In addition, a soft composition may become lumpy, and may cause problems such as the composition fusing in a hopper in an injection molding method, or the previously molded tablets fusing in a transfer molding method, or even changes in shape and becoming unable to fit into the tablet insertion hole in a transfer molding machine. The present invention achieves both fluidity and handling, thereby providing an excellent effect of high productivity.
[0037] <Production method of unsaturated polyester> The unsaturated polyester used in the present invention can be, for example, obtained by subjecting an unsaturated polybasic acid, a saturated polybasic acid, and glycols to a known dehydration condensation reaction, and can usually have an acid value of 2 to 40 mg-KOH / g. In producing the unsaturated polyester, the selection and combination of the acid components of the unsaturated polybasic acid and the saturated polybasic acid, the selection and combination of the glycols, and the blending ratio thereof can be appropriately selected to obtain an unsaturated polyester having crystallinity.
[0038] Examples of the unsaturated polybasic acids include maleic acid, maleic anhydride, fumaric acid, citraconic acid, mesaconic acid, itaconic acid, tetrahydrophthalic acid, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, and glutaconic acid.
[0039] Examples of the saturated polybasic acids include phthalic acid, phthalic anhydride, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, endomethylenetetrahydrophthalic anhydride, HET acid, tetrabromophthalic anhydride, 1,4-cyclohexanedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, and 1,8-naphthalenedicarboxylic acid.
[0040] Examples of glycols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, propylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, neopentyl glycol, 1,3-butanediol, hydrogenated bisphenol A, bisphenol A propylene oxide compound, cyclohexanedimethanol, dibromo neopentyl glycol, isosorbide, isomanide, and tricyclodecane dimethanol.
[0041] In the present invention, among the crystalline unsaturated polyesters, unsaturated polyesters using fumaric acid as the unsaturated polybasic acid, isophthalic acid or terephthalic acid as the saturated polybasic acid, and using ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, or 1,4-cyclohexanedimethanol as the main glycol component are preferred.
[0042] <Method for producing epoxy (meth)acrylate> The epoxy (meth)acrylate used in the present invention can be produced by a method known per se. By appropriately selecting an epoxy resin and an unsaturated monobasic acid in the presence or absence of a known inhibitor and a known esterification catalyst, in an inert gas stream or in an air atmosphere, a crystalline epoxy (meth)epoxy acrylate can be obtained. If necessary, other radical polymerizable monomers or organic solvents can be added to the reaction system in order to reduce the melt viscosity of the reaction system.
[0043] The epoxy (meth)acrylate in the present invention can be, for example, an epoxy (meth)acrylate having an acrylate or methacrylate double bond at the molecular end obtained by addition reaction of acrylic acid or methacrylic acid with an epoxy resin having two or more glycidyl ether groups in one molecule. It may be an epoxy (meth)acrylate resin in which an epoxy (meth)acrylate is dissolved in a radical polymerizable monomer and / or a radical polymerizable multimer. The epoxy resin having two or more glycidyl ether groups in one molecule may be, for example, a bisphenol type epoxy resin from bisphenol A, bisphenol F, bisphenol S, etc., or their derivatives, a bixylenol type epoxy resin from bixylenol and its derivatives, a biphenol type epoxy resin from biphenol and its derivatives, a naphthalene type epoxy resin from naphthalene and its derivatives, a novolac type epoxy resin, or an aliphatic epoxy resin, which may be used alone or in a mixture of two or more kinds. The epoxy equivalent, which is a measure of the molecular weight of the epoxy resin, is preferably 125 to 4,000 eq / g.
[0044] <Method for producing urethane (meth)acrylate> The urethane (meth)acrylate in the present invention can be, for example, a urethane acrylate having an acrylate or methacrylate double bond at the molecular end, which is obtained by reacting a polyalcohol and / or polyester polyol and / or polyether polyol having two or more hydroxyl groups in one molecule with a diisocyanate to produce an isocyanate at the molecular end, and / or by reacting one or more isocyanates in one molecule with a compound having an alcoholic hydroxyl group and one or more acrylate groups or methacrylate groups, or by first reacting a compound having an alcoholic hydroxyl group and one or more acrylate groups or methacrylate groups with a diisocyanate so that an isocyanate group remains, and then reacting the remaining isocyanate group with a polyalcohol and / or polyester polyol and / or polyether polyol having two or more hydroxyl groups in one molecule. In the production of urethane (meth)acrylate, a combination of isocyanate and polyalcohol and / or polyester polyol and / or polyether polyol, and a compound having an alcoholic hydroxyl group and one or more acrylate or methacrylate groups are appropriately selected to produce a urethane (meth)epoxy acrylate having crystallinity. Urethane acrylate or urethane methacrylate may be dissolved in a radical polymerizable monomer and / or a radical polymerizable polymer such as styrene or diethylene glycol dimethacrylate to produce a urethane (meth)acrylate resin. These may be used alone or in a mixture of two or more kinds.
[0045] Examples of the compound having an alcoholic hydroxyl group and one or more acrylate or methacrylate groups include hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, phenoxyhydroxypropyl (meth)acrylate, trimethylolpropane di(meth)acrylate, and dipropylene glycol mono(meth)acrylate.
[0046] Examples of the polyalcohols having two or more hydroxyl groups in one molecule include neopentyl glycol, ethylene glycol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, propylene glycol, diethylene glycol, dipropylene glycol, trimethylene glycol, hydrogenated bisphenol A, bisphenol A ethylene oxide adduct, bisphenol A propylene oxide adduct, etc. Examples of the polyester polyols having two or more hydroxyl groups in one molecule include neopentyl glycol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, trimethylene glycol, hydrogenated bisphenol A, bisphenol A ethylene oxide adduct, etc. The polyether polyol having two or more hydroxyl groups in one molecule may be, for example, a saturated polyester polyol having a molecular weight of 400 to 2,000 obtained by a dehydration condensation reaction between a polyalcohol such as a bisphenol A adduct or a bisphenol A propylene oxide adduct and a polybasic acid such as adipic acid, phthalic acid (anhydride), isophthalic acid, terephthalic acid, trimellitic acid, etc., and the polyether polyol having two or more hydroxyl groups in one molecule may be, for example, a polyethylene glycol or polypropylene glycol having a molecular weight of 300 to 4,000 obtained by a ring-opening reaction of ethylene oxide or propylene oxide, or a polycaprolactone obtained by a ring-opening reaction of caprolactone, either alone or in combination of two or more kinds.
[0047] Examples of the compound having two or more isocyanate groups in one molecule include aromatic and / or aliphatic polyisocyanate compounds, such as tolylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,6-hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, trifunctional isocyanate having an isocyanurate ring obtained by trimerizing a bifunctional isocyanate compound, biuret, adduct, commercially available isocyanate prepolymer modified with polyol, etc. These compounds may be used alone or in combination of two or more.
[0048] <Method for producing polyester (meth)acrylate> The polyester (meth)acrylate in the present invention may be, for example, a polyester acrylate or polyester methacrylate having an acrylate or methacrylate double bond at the molecular end obtained by esterification of a polyester polyol with acrylic acid or methacrylic acid, or by reaction of an acid-terminated polyester with an acrylate or methacrylate having a glycidyl group. In the production of a polyester (meth)acrylate, a polyester (meth)acrylate having crystallinity can be obtained by appropriately selecting a polyester polyol and an acrylic acid or methacrylic acid, or an acid-terminated polyester and an acrylate or methacrylate having a glycidyl group. The polyester acrylate or polyester methacrylate may be dissolved in a radical polymerizable monomer and / or a radical polymerizable polymer, such as styrene or diethylene glycol dimethacrylate, to form a polyester acrylate resin or polyester methacrylate resin. These may be used alone or in a mixture of two or more kinds.
[0049] <Method for producing polyether (meth)acrylate> In addition, the polyether (meth)acrylate in the present invention can be, for example, a polyether acrylate or polyether methacrylate having an acrylate or methacrylate double bond at the molecular end obtained by esterification of a polyether polyol with acrylic acid or methacrylic acid, or by reaction of an acid-terminated polyether with an acrylate or methacrylate having a glycidyl group. In the production of a polyether (meth)acrylate, a polyester (meth)acrylate having crystallinity can be obtained by appropriately selecting a polyether polyol and acrylic acid or methacrylic acid, or an acid-terminated polyester and an acrylate or methacrylate having a glycidyl group. The polyether acrylate or polyether methacrylate may be a polyether acrylate resin or polyether methacrylate resin in which the polyether acrylate or polyether methacrylate is dissolved in a radical polymerizable monomer and / or radical polymerizable polymer such as styrene or diethylene glycol dimethacrylate. These can be used alone or in a mixture of two or more kinds.
[0050] In a preferred embodiment, the crystalline radically polymerizable monomer that is solid at 30 to 150°C in the present invention is ethoxylated isocyanuric acid triacrylate (melting point: about 50°C), polyethylene glycol di(meth)acrylate (melting point: 35 to 53°C), methoxypolyethylene glycol (meth)acrylate (melting point: 33 to 40°C), behenyl acrylate (melting point: 46°C), tetramethyl piperidinyl methacrylate (melting point: 56 to 60°C), trimethallyl isocyanurate ... The crystalline radical polymerizable compound may contain one or more selected from the group consisting of acetonitrile (melting point 83 to 87°C), diacetone acrylamide (melting point about 56°C), itaconic acid dimethyl ester (melting point 36°C), vinyl stearate (melting point 36°C), N-vinyl carbazole (melting point 67°C), N-methylolacrylamide (melting point 71 to 75°C), acrylamide (melting point 84°C), tolylenediaryl carbamate (melting point 85 to 110°C), maleimide (melting point 93°C), acenaphthylene (melting point 95°C), etc. Use of these crystalline radical polymerizable compounds improves handling.
[0051] The radical polymerizable monomer in the present invention may be a liquid radical polymerizable monomer at room temperature within a range that does not impair the present object. For example, vinyl aromatic compounds such as styrene monomer having a vinyl group, α-methylstyrene, vinyltoluene, and α-chlorostyrene; vinyl esters such as vinyl acetate, vinyl propionate, vinyl lactate, vinyl butyrate, and Veova Monomer (manufactured by Shell Chemical Co.); and (meth)acrylic esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, methyl methacrylate, ethyl methacrylate, and n-butyl methacrylate.
[0052] Also usable are radically polymerizable monomers having two or more functionalities, such as triallyl cyanurate, diethylene glycol dimethacrylate, diallyl tetrabromophthalate, phenoxyethyl acrylate, 2-hydroxyethyl acrylate, 1,6-hexanediol diacrylate, diallyl phthalate having an allyl group, diallyl maleate, diallyl fumarate, triallyl isocyanurate, etc. These radically polymerizable monomers may be used alone or in combination of two or more kinds.
[0053] The radical polymerizable polymer in the present invention may be a diallyl phthalate prepolymer, a tyrenic prepolymer, an epoxy prepolymer, a urethane prepolymer, or an acrylate prepolymer. These radical polymerizable polymers may be used alone or in combination of two or more kinds.
[0054] In the crystalline radically polymerizable composition for molding of the present invention, an inorganic filler can be blended. Examples of the inorganic filler include calcium carbonate, magnesium carbonate, barium carbonate, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, magnesium oxide, alumina, silica, zinc oxide, mica, talc, aluminum nitride, and boron nitride. Among these, alumina, magnesium oxide, and aluminum nitride are preferred from the viewpoint of thermal conductivity. Among these, aluminum nitride is most preferred, and the amount added is preferably 0.1 to 15% by mass. Among these, 2 to 10% by mass is most preferred. These may be used alone, or two or more may be used in combination. The reason for the above range is that if the amount is less than 0.1% by mass, the thermal conductivity is low and the heat dissipation property is reduced, and if the amount is more than 15% by mass, the viscosity of the composition is high and there is a risk of the composition being left unfilled during molding.
[0055] The inorganic filler can have an average particle size of 150 μm or less, preferably 0.01 to 80 μm. By using an inorganic filler having the above average particle size, a crystalline radically polymerizable composition for molding having excellent fluidity and strength during molding can be obtained. The reason for the above range is that it is more advantageous to use a large inorganic filler as a thermal conductive material. When a large amount of inorganic filler with a small average particle size is used, the resin has low thermal conductivity, so there is a risk of heat resistance and the thermal conductivity of the molded product being reduced. Therefore, it is more advantageous to use an inorganic filler with a large average particle size in terms of thermal conduction, but an inorganic filler that is too large may cause appearance (surface irregularities) and may not be able to be filled into fine parts, and from this perspective, the size can be narrowed down to a certain degree.
[0056] The average particle size is measured by the laser diffraction method, and the JIS standard is JIS Z 8825-1. Note that this JIS Z 8825-1 was abolished on December 20, 2013, and replaced by JIS Z 8825. JIS Z 8825-1 is called Particle size analysis - Laser diffraction method.
[0057] In the crystalline radically polymerizable molding composition of the present invention, various additives that adhere to the inorganic filler and reinforcing material, such as a (meth)acrylate compound having a polar group and a coupling agent, can be blended.
[0058] The (meth)acrylate compound having a polar group is not particularly limited, but may be, for example, a (meth)acrylate compound in which a substituent containing an atom other than carbon or hydrogen is ester-bonded, and examples of the substituent include a hydroxyl group, an epoxy group, a glycidyl ether group, a tetrahydrofurfuryl group, an isocyanate group, a carboxyl group, an alkoxysilyl group, a phosphate ester group, a lactone group, an oxetane group, a tetrahydropyranyl group, and an amino group. The coupling agent is not particularly limited, but may be, for example, a silane coupling agent or a titanate coupling agent, and examples of the silane coupling agent that may be used include, for example, an epoxy silane, an amino silane, a cationic silane, a vinyl silane, an acrylic silane, a mercapto silane, and a composite system thereof.
[0059] Among these, the acrylic silane coupling agent is preferred from the viewpoint of improving strength, but any other additives can be used as long as they do not impair the object of the present invention.
[0060] In the crystalline radically polymerizable molding composition of the present invention, as the radical polymerization initiator, an organic peroxide or a polymerization inhibitor which is usually used in an unsaturated polyester resin composition or a radically polymerizable composition can be used.
[0061] Examples of organic peroxides include t-butylperoxy-2-ethylhexyl monocarbonate, 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)cyclohexane, 1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane, t-butylperoxyoctoate, benzoyl peroxide, methyl ethyl ketone peroxide, acetylacetone peroxide, t-butylperoxybenzoate, dicumyl peroxide, etc. These may be used alone or in combination of two or more.
[0062] Among these, from the viewpoints of molding conditions and storage stability, it is preferable to use an organic peroxide having a 10-hour half-life temperature of 90° C. or higher, and specifically, dicumyl peroxide can be suitably used.
[0063] Polymerization inhibitors include hydroquinone, monomethyl ether hydroquinone, toluhydroquinone, di-t-4-methylphenol, monomethyl ether hydroquinone, phenothiazine, t-butylcatechol, parabenzoquinone, pyrogallol and other quinones, 2,6-di-t-butyl-p-cresol, 2,2-methylene-bis-(4-methyl-6-t-butylphenol), 1,1,3-tris-(2-methyl-4-hydroxy-5-t-butylphenyl) Examples of the suitable phenol compounds include phenolic compounds such as 2,2,6,6-tetramethylpiperidine-1-oxyl, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-oxo-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-carboxy-2,2,6,6-tetramethylpiperidine-1-oxyl, and 2,2,6,6-tetramethylpiperidine-1-oxyl. By using these, it is possible to suppress the increase in viscosity during the filling step at the time of molding, and to obtain a radical polymerizable composition having a low melt viscosity. These may be used alone, or two or more of them may be used in combination.
[0064] The crystalline radically polymerizable composition for molding of the present invention can be blended with a reinforcing material. By using a reinforcing material, the crystalline radically polymerizable composition for molding can be made to have excellent strength characteristics and dimensional stability.
[0065] The reinforcing material used in the present invention is usually glass fiber, which is used in fiber-reinforced plastics such as BMC (bulk molding compound) and SMC (sheet molding compound), but is not limited to glass fiber and can be other materials. It can be used.
[0066] Examples of glass fibers include E glass (alkali-free glass for electrical use), C glass (alkali-containing glass for chemical use), A glass (acid-resistant glass), S glass (high-strength glass), etc., which are made from silicate glass or borosilicate glass, and these can be used in the form of long fibers (rovings), short fibers (chopped strands), or milled fibers. Furthermore, these glass fibers can also be used after surface treatment.
[0067] In the crystalline radically polymerizable molding composition of the present invention, other inorganic fillers can be appropriately blended within the limits that do not impair the properties of the molded article.
[0068] These include oxides and their hydrates, inorganic foam particles, hollow particles such as silica balloons, and the like.
[0069] In the crystalline radically polymerizable molding composition of the present invention, a thermoplastic resin can be appropriately blended within a range that does not impair the properties of the molded article.
[0070] These include thermoplastic resins such as polystyrene, acrylic resins, polyvinyl acetate, saturated polyesters, styrene-butadiene rubbers, and organic foam particles.
[0071] In the crystalline radical polymerizable composition for molding of the present invention, a release agent can be used. As the release agent, waxes such as fatty acid-based, fatty acid metal salt-based, and mineral-based, which are generally used in thermosetting resins, can be used, and in particular, fatty acid-based, fatty acid metal salt-based, and waxes having excellent heat discoloration resistance can be preferably used.
[0072] Specific examples of these release agents include stearic acid, zinc stearate, aluminum stearate, calcium stearate, paraffin wax, etc. These release agents may be used alone or in combination of two or more.
[0073] As the mold release agent, an external mold release agent such as a type that is sprayed or applied to the mold or a molding material containing a mold release agent can be used as required.
[0074] In the crystalline radically polymerizable molding composition of the present invention, a flame retardant can be used. As the flame retardant, halogen-based, phosphorus-based, nitrogen-based, and composite organic flame retardants, and inorganic flame retardants such as metal hydroxides, antimony-based, red phosphorus-based, silicone-based, and borate can be used. Furthermore, as these flame retardants, additive-type flame retardants and reactive-type flame retardants that react with resin and are incorporated into the resin skeleton can also be used. These flame retardants may be used alone or in combination of two or more.
[0075] In the present invention, in addition to these blending components, curing catalysts for adjusting the curing conditions of the crystalline radically polymerizable composition, polymerization inhibitors, colorants, thickeners, wetting and dispersing agents, surface conditioners, viscosity reducers, flow modifiers, other organic additives, inorganic additives, and the like may be blended as necessary.
[0076] <Method for producing crystalline radically polymerizable composition> The crystalline radically polymerizable composition for molding of the present invention can be produced by blending the respective components, mixing them thoroughly and uniformly using a mixer, blender or the like, and then preparing and granulating them in a kneader or extruder capable of heating and pressurizing.
[0077] The granular material of the present invention is characterized in that it comprises the crystalline radically polymerizable composition for molding of the present invention.
[0078] The molded article of the present invention is characterized in that it is obtained by molding a granular material made of the crystalline radically polymerizable composition for molding of the present invention. The molded article can be molded by a conventional molding method for various thermosetting compositions.
[0079] In addition, since the crystalline radically polymerizable composition for molding of the present invention is a dry molding method and has good thermal stability when melted, a melt heating molding method such as injection molding, injection compression molding, transfer molding, compression molding, or hot melt molding can be suitably used as a molding method.
[0080] Among these, injection molding using an injection molding machine and transfer molding using a transfer molding machine are particularly suitable, as injection molding shortens the molding time, while transfer molding allows many molded articles to be molded at once, making it possible to produce molded articles with complex shapes.
[0081] <Molded body and method for producing the molded body> The molded article of the present invention can be produced by molding a molded article using the crystalline radical polymerizable composition for molding of the present invention. Here, the crystalline radical polymerizable composition for molding of the present invention may be one in which all the components constituting the crystalline radical polymerizable composition are separately heated and kneaded in advance, or one in which some or all of the components are mixed and heated and kneaded just before injection into a mold.
[0082] The temperature and pressure of the crystalline radical polymerizable composition when injected into the mold are not particularly limited, but when an injection molding machine is used, a crystalline radical polymerizable composition temperature of 60 to 130°C, a mold temperature of 130 to 190°C, and a crystalline radical polymerizable composition pressure of 0.1 to 10 MPa are preferable, whereas when a transfer molding machine is used, a mold temperature of 130 to 190°C and a crystalline radical polymerizable composition pressure of 0.1 to 10 MPa are preferable, as these reduce damage to automobile drive motors. EXAMPLES
[0083] Hereinafter, one embodiment of the present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.
[0084] <Production Example of Radical Polymerizable Composition for Molding> Examples 1 to 4 and Comparative Examples 1 to 2 The crystalline or amorphous radically polymerizable compositions of Examples 1 to 4 and Comparative Examples 1 and 2 shown in Table 1 below were mixed in the amounts shown and homogenized using a kneader capable of pressurizing, heating and cooling, and then the mixture was fed into an extruder and granulated by a hot-cut method. Some of the granular and bulk radically polymerizable compositions were powderized using a pulverizer.
[0085] The obtained radical polymerizable composition was used to prepare test specimens by transfer molding using a hydraulic molding machine (manufactured by Toho Press Manufacturing Co., Ltd.). The mold temperature was 165°C, and the curing time was 180 seconds or until the time when a test specimen could be obtained was reached, to prepare the test specimens. The physical properties of the molded test specimens (molded bodies) were evaluated by the methods described below, and the results are shown in Table 1 below.
[0086] The following components were used as the blending ingredients: (1) Radical polymerizable compound 1. Crystalline radical polymerizable compound 2: Urethane methacrylate (1,6-hexamethylene diisocyanate to 2-hydroxyethyl methacrylate adduct) (2) Radical polymerizable monomer 2. Radical polymerizable monomer 2: Ethoxylated isocyanuric acid triacrylate (A-9300, manufactured by Shin-Nakamura Chemical Co., Ltd.)
[0087] (3) Inorganic filler 1. Inorganic filler 1: Fused silica (manufactured by Denka Co., Ltd., average particle size 24 μm) 2. Inorganic filler 2: Aluminum nitride (Tokuyama Corporation)
[0088] (4) Additives 1. Coupling agent: Methacrylic silane (KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) 2. Radical polymerization initiator: Dicumyl peroxide (Percumyl D, manufactured by NOF Corporation) 3. Release agent: Zinc stearate (NOF Corp. GF-200) 4. Polymerization inhibitor: Perabenzoquinone (PBQ, manufactured by Seiko Chemical Co., Ltd.) 5. Colorant: Carbon black (CB40, manufactured by Mitsubishi Chemical Corporation)
[0089] [Table 1]
[0090] <Compound characteristics, composition characteristics, physical property evaluation methods>
[0091] (1) Thermal conductivity The measurement method was ISO22007-2. Thermal conductivity was measured using molded bodies of the crystalline radical polymerizable compositions of Examples 1 to 4 and Comparative Examples 1 to 2 shown in Table 1. The molded bodies of the radical polymerizable resin compositions were cut into 4 mm squares, and the specific heat was measured using a DSC (Shimadzu Corporation, Differential Scanning Calorimeter DSC-60). In addition, the molded bodies of the radical polymerizable resin compositions were cut into 4 mm squares, and the specific gravity was measured using a specific gravity measuring device (A&D Corporation, Specific Heat Measurement Kit AD-1653). In addition, the molded bodies of the radical polymerizable resin compositions were cut into W30 × D5 × 0.5 mmt, and the thermal diffusivity was measured in the W30 direction using a thermal diffusivity measuring device (Advance Riko Corporation, Optical AC Method Thermal Diffusivity Measuring Device). The thermal conductivity was calculated from the measured specific heat, specific gravity, and thermal diffusivity. The results are shown in Table 1. The target thermal conductivity was set to 1.0 W / m·K or more. However, even if the strict standards mentioned above are not met, a condition of less than 1.0 W / m K may be sufficient depending on the desired application, required quality, etc., so this should be considered as a guideline.
[0092] (2) Melt Viscosity The melt viscosity of the crystalline radically polymerizable compositions of Examples 1 to 4 and Comparative Examples 1 to 2 shown in Table 1 was measured using a BMC viscometer (BMC-100T-3, manufactured by Sanki Sangyo Co., Ltd.). The radically polymerizable composition was placed in a cylinder sample insertion hole equipped with a die having a diameter of 2.0 mm and a length of 10 mm and heated to 90°C, and after preheating for 900 seconds, the piston was pressurized at a speed of 10 mm / min to cause the radically polymerizable composition to flow out of the nozzle of the die, and the melt viscosity of the composition at a shear rate of 10 / s was obtained from the point where the linearity was good. The results are shown in Table 1. The target viscosity was 0.5 to 10.0 Pa·s, and compositions with a viscosity of 0.5 to 5.0 Pa·s were rated as excellent, 1.0 to 10.0 Pa·s as good, and compositions with a viscosity of less than 0.5 Pa·s and / or more than 10.0 Pa·s as acceptable. However, depending on the desired application and required quality, a viscosity of less than 0.5 Pa s and / or more than 10.0 Pa s may meet the conditions even if the above strict standards are not met, so these standards should be considered as a guideline.
[0093] <Evaluation Results> As shown in Table 1, Examples 1 to 4 of the crystalline radically polymerizable molding composition of the present invention were solid at 23° C. and therefore had excellent handleability and good thermal conductivity.
[0094] As described above, it has been found that the crystalline radically polymerizable molding composition containing at least a crystalline radically polymerizable compound is excellent in thermal conductivity and handleability. [Industrial Applicability]
[0095] The crystalline radically polymerizable molding composition of the present invention and molded articles made using the same have excellent thermal conductivity and are therefore suitable for use as molded articles for automobile parts, electric and electronic parts, in-vehicle electronic control units, ignition coils, harness ends, and power semiconductor elements.
Claims
1. The crystalline radically polymerizable composition for molding contains a crystalline radically polymerizable compound having at least a glass transition point and a melting point, an inorganic filler, a silane coupling agent, and a radical polymerization initiator, and is characterized in that the crystalline radically polymerizable composition contains 0.1 to 15 mass % of aluminum nitride as an inorganic filler and is a solid at 23°C.
2. The crystalline radically polymerizable composition for molding according to claim 1, characterized in that the crystalline radically polymerizable compound contains one or more selected from the group consisting of crystalline unsaturated polyesters, crystalline epoxy (meth)acrylates, crystalline urethane (meth)acrylates, crystalline polyester (meth)acrylates, crystalline polyether (meth)acrylates, crystalline radically polymerizable monomers, and crystalline radically polymerizable multimers.
3. 3. The crystalline radically polymerizable composition for molding according to claim 1, wherein the crystalline radically polymerizable compound has a melting point in the range of 30 to 150°C.
4. The crystalline radically polymerizable composition for molding according to any one of claims 1 to 3, characterized in that the inorganic filler is present in an amount of 40 to 95 mass % based on the total amount of the crystalline radically polymerizable composition.
5. The crystalline radically polymerizable composition for molding according to any one of claims 1 to 4, characterized in that the ratio of the crystalline radically polymerizable compound to the total amount of the radically polymerizable compounds is 25 parts by mass or more.
6. 6. The crystalline radically polymerizable composition for molding according to claim 1, wherein the crystalline radically polymerizable compound has a weight average molecular weight of 70 to 100,000.
7. A granular material comprising the crystalline radically polymerizable composition for molding according to any one of claims 1 to 6.
8. A molded article obtained by molding granules made from the crystalline radically polymerizable composition for molding according to claim 7.
9. 9. The molded article according to claim 8, wherein the molded article has a thermal conductivity of 1.0 W / m·K or more.
10. A method for producing a molded body, comprising a molding step of molding a molded body by any one of injection molding, transfer molding, compression molding, and hot melt molding using the granules consisting of the crystalline radical polymerizable composition for molding according to claim 7.
Citation Information
Patent Citations
Box frame body fabricating machine
JP1982027628A
Bus contention control system
JP1985041157A